Descriptive review of acute cholecystitis: Japan‐Taiwan collaborative epidemiological study. (14th May 2017) - Yokoe, Masamichi; Takada, Tadahiro; Hwang, Tsann‐Long; Endo, Itaru; Akazawa, Kohei; Miura, Fumihiko; Mayumi, Toshihiko; Mori, Rintaro; Chen, Miin‐Fu; Jan, Yi‐Yin; Ker, Chen‐Guo; Wang, Hsiu‐Po; et al.
Abstract: Background: Since the publication of the Tokyo Guidelines (TG13) for the management of acute cholecystitis (AC), multidirectional studies have been published. However, epidemiological research about AC with big data was not projected. The aim of this study was to reveal the actual clinical conditions of AC. Method: The study was designed as an international multicenter retrospective study of AC in Japan and Taiwan from 2011 to 2013. The factors investigated comprised data related to demographic, history, physical examinations, laboratory and imaging findings. Based on these data, we investigated the various values of AC, and real situation with respect to severity and treatment. Results: A total of 5, 459 patients with AC were reviewed. Thirty‐day mortality rate was 1.1%. Based on the diagnostic criteria, 4, 088 patients had a definite diagnosis and 291 had a suspected diagnosis. According to the severity grading, 939 patients were classified as Grade III, 2, 308 as Grade II, and 2, 130 as Grade I. Cholecystectomy was performed in total of 4, 266 patients and 2, 765 patients had laparoscopic cholecystectomy. The main etiologies were gallbladder stones in 4, 623 cases. Conclusion: This epidemiological study with large population will undoubtedly contribute to establish the best practice for managing AC worldwide. Abstract : Highlight In this international multicenter retrospective study of acute cholecystitis in Japan and Taiwan, Yokoe and colleagues conducted an epidemiological review of 5, 459 cases. The big data obtained in this study revealed the mortality rate of acute cholecystitis, the distribution of TG13 severity grading and the implementation rate of laparoscopic cholecystectomy.